Emancipatory Indigenous social innovation: Shifting power through culture and technology. (1st February 2018) - Henry, Ella; Newth, Jamie; Spiller, Chellie
Abstract: This paper explores the emancipatory impulse of Indigenous social innovation and social enterprise. Indigenous approaches to solving social disparities reflect a perpetual search for innovative ways to change the circumstances of Māori. Power is an understudied dimension of social innovation and social enterprise. This paper explores the power dynamics that structure the disadvantage and marginalisation that cause populations to be underserved by markets and that limit their access to resources. We highlight that it is not power per se that enables social change: rather, it is power shifts . Through a single, richly contextualised case study of a well-known Māori social innovator, Dr Lance O'Sullivan, we reveal and illustrate the nuances of Indigenous entrepreneurship in the Far North of Aotearoa New Zealand. The case epitomises the transformative impact a social entrepreneur can have on the provision of healthcare amid market and policy failures.